Synthesis of New Isatin-3-[N2-(3-Arylideneamino-4-hydroxybenzoyl)]hydrazones as Antioxidant and Cytotoxic Agents - Venkateshwar Rao, J.; Sarangapani, M. (Asian Journal of Chemistry, 2010)
In an effort to establish twenty five new isatin-3-[N2-(3- arylideneaimino-4-hydroxybenzoyl)]hydrazones (4a-y), isatin-3-[N2-(3-amino-4-hydroxybenzoyl)]hydrazones (3a-e) were condensed with five different aromatic aldehydes viz., benzaldehyde, 4-chlorobenzaldehyde, salicylaldehyde, anisaldehyde and veratraldehyde. The compounds, isatin-3-[N2-(3- amino-4-hydroxybenzoyl)]hydrazones (3a-e) were prepared from 3-amino-4-hydroxy benzoic acid hydrazide (2) by reacting with different isatins viz., isatin, 5 chloroisatin, 5-methylisatin, 5-bromoisatin and 5-flouroisatin in presence of ethanol. The compounds (4a-y) were screened for their in vitro antioxidant activity by 1,1-diphenyl-2-picrylhydrazil (DPPH) method and the cytotoxic activity by 3-(4,5-dimethyl thiazol-2,5-diphenyl)- tetrazolium bromide (MTT) assay method using HBL-100 cell lines and HeLa cell lines. All the 25 compounds showed antioxidant activity with IC50 values in the range of 7.38 to 12.47 μM. Most significant of them was found to be the compound 4r (R = Br, R' = OH) showed highest percentage of free radical scavenging activity at 7.38 μM. Compound 4q (R = Br, R'' = Cl) was found to be relatively more cytotoxic agent against HeLa cell lines and HBL-100 cell lines with IC50 values of 192.31 and 198.18 μM, respectively.